Supporting youths in global crises: an analysis of risk and resources factors for multiple health complaints in children and adolescents during the COVID-19 pandemic - Habermann, Karoline; Napp, Ann-Kathrin; Reiß, Franziska; Kaman, Anne; Erhart, Michael; Ravens-Sieberer, Ulrike (Frontiers in Public Health, 2025)
IntroductionThe number of global crises increased in recent years, significantly affecting the health and well-being of children and adolescents worldwide. Awareness of these global crises and their impact on health and well-being has risen since the COVID-19 pandemic. Research indicates that some children and adolescents are more vulnerable to the challenges resulting from these crises than others. This study examines the risk and resources factors for multiple health complaints (MHC) in children and adolescents in Germany during the COVID-19 pandemic.MethodsWe analyzed data from the German population-based longitudinal COPSY (COvid-19 and PSYchological Health) study. A total of 1,673 children and adolescents aged 11 years and older and their parents participated in at least one of the five survey waves between 2020 and 2022. We assessed MHC using the international Health Behavior in School-aged Children Symptom Checklist (HBSC-SCL), which includes four somatic complaints (e.g., headache, abdominal pain) and four psychological complaints (e.g., feeling low, sleeping difficulties). We conducted a mixed model panel regression analysis to examine longitudinal changes in MHC and identified sociodemographic, psychosocial, and pandemic-related risk factors and resources.ResultsOur results revealed increased MHC throughout the COVID-19 pandemic. Girls, single-parent children and adolescents, as well as children and adolescents of mentally ill or highly burdened parents, were at particular risk. A higher subjective perceived burden of the pandemic and COVID-19-related worries were significantly associated with a higher level of MHC. Personal resources, a positive family climate, and more perceived social support were significantly associated with a lower level of MHC.DiscussionThis paper highlights the vulnerability of children and adolescents in a global crisis, such as the COVID-19 pandemic. The results provide a scientific foundation for targeted health promotion and intervention strategies to protect and maintain the health and well-being of young people in future crises.